Fabric Electronics: Autocatalytic Metallization of Fabrics Using Si Ink, for Biosensors, Batteries and Energy Harvesting (Adv. Funct. Mater. 1/2019). (2nd January 2019) - Grell, Max; Dincer, Can; Le, Thao; Lauri, Alberto; Nunez Bajo, Estefania; Kasimatis, Michael; Barandun, Giandrin; Maier, Stefan A.; Cass, Anthony E. G.; Güder, Firat
Abstract : In article number1804798, Max Grell, Firat Guder, and co‐workers describe a method for depositing a wide range of metals inside fabrics which they call Si ink‐enabled autocatalytic metallization. Without requiring surface modification, the method provides access to devices as diverse as antennas, batteries, biosensors, or Raman spectroscopy substrates. Future research might bring many more applications for this highly adaptable method.